A new approach to ASP flooding in high saline and hard carbonate reservoirs - Kalwar, S.A. (Society of Petroleum Engineers, 2014)
Chemical Enhanced Oil Recovery (CEOR) has come into focus as a highly effective and versatile EOR method due to recent advances in the technology. However, CEOR particularly Alkali-Surfactant-Polymer (ASP) flooding is challenging in carbonate reservoirs. The main constraints are the undesired minerals such as calcite, dolomite, anhydrite and gypsum consisted of divalent ions. The minerals complex with injected chemicals and form precipitates that cause formation damage and scale formation in wells and surface facilities. This study presents a new Acid-Alkali-Surfactant-Polymer (AASP) flooding formulation as an alternative to conventional ASP flooding. AASP included acrylic acid as a precipitation inhibitor. The new formulation was compatible with the hard brine composition of 59,940 ppm TDS (with 2762 ppm divalent ions) for 30 days at 80 Â°C. AASP combination also provided acceptable interfacial tension and slug viscosity required for flooding in the presence of hard brine. Additionally, more than 30 Origional Oil in Place (OOIP) was recovered in the natural imbibition tests. Injecting 0.5PV of the optimum AASP formulation slug gave 18.9 OOIP to waterflooding in the coreflood tests. Thus, AASP flooding formulation is viable for suppressing the limitations of ASP flooding in carbonate reservoirs. Although, precipitation inhibitor increases the cost of chemical slug by adding several hundred parts per million (ppm) of inhibitor, significant cost savings will be realized because of the reductions in workover jobs and associated lost of production. Further, AASP flooding formulation also eliminates the need to soften the mixing brine. This will result in expanding the CEOR application to more challenging carbonate reservoirs and reduce the softening cost for mixing water. Copyright Â© 2014, International Petroleum Technology Conference.